The association between numerical magnitude processing and mental versus algorithmic multi-digit subtraction in children. (February 2015) - Linsen, Sarah; Verschaffel, Lieven; Reynvoet, Bert; De Smedt, Bert
Abstract: When solving multi-digit subtraction problems, children are instructed to use different types of calculation methods, such as mental and algorithmic computation. It has been contended that these two methods differentially rely on numerical magnitude processing, an assumption that has not yet been tested empirically. We therefore aimed to examine the association between the ability to represent numerical magnitudes and mental and algorithmic computation. This was done by conducting a study in fourth grade children using a symbolic and a nonsymbolic numerical magnitude comparison task and two arithmetic tasks: one in which children had to use mental computation and another one in which they were required to apply algorithmic computation. Our results show that both calculation methods rely on numerical magnitude processing, however, the association is larger for mental than for algorithmic computation. Highlights: Do mental and algorithm computation differentially rely on basic number sense? Both calculation methods rely on numerical magnitude processing. Association is larger with mental than with algorithmic computation.